Creación del centro de promoción turística y difusión cultural "Raíces Nativas" - Castañeda Arias, Diego Leonardo (2015)
Tourism has become a tool of strengthening and re-valuation of culture, is directly responsible for the development of various social actors; particularly the city of Otavalo, is an attractive globally recognized by national and international tourists, current trends tell us that tourists, looking on their trips in knowledge about the culture of the place you visit and during their stay, looking for authenticity in the products and / or services that consume and provide an understanding of the historical reality of the attractions; why there is talk of an increasingly demanding and sophisticated looking for first-rate attractions demand..